Қ.МӘТМУРАТОВТЫҢ «ТЕРБЕНБЕС» РОМАНЫНДА ПОРТРЕТЛЕРДИҢ ИНДИВИДУАЛЛЫҚ ҲӘМ УЛЫЎМАЛЫҚ ҚӘСИЙЕТЛЕРИ - Алламуратов, Ғ.А. (ILIM hám JÁMIYET, 2021)
The article examines the individual and general characteristics of the portraits of the novel. The individual and general features of the portrait play an important role in the creation of the image. These features play a key role in the novel's faithful portrayal of space and time. In our work, based on the scientific analysis of the portrait in the novel "Terbenbes" by the writer K. Matmuratov, we try to determine his image-making skill, originality.